Mechanosynthesis of higher-order cocrystals: tuning order, functionality and size in cocrystal design - Ng, Zi Xuan (2022)
The ability to rationally design and predictably construct crystalline solids has been the hallmark of crystal engineering research. To date, numerous examples of multicomponent crystals comprising organic molecules have been reported. However, the crystal engineering of cocrystals comprising both organic and inorganic chemical units is still poorly understood and mostly unexplored. Here, we report a new diverse set of higher-order cocrystals (HOCs) based on the structurally versatile-yet largely unexplored-phosph(V/V)azane heterosynthon building block. The novel ternary and quaternary cocrystals reported are held together by synergistic and orthogonal intermolecular interactions. Notably, the HOCs can be readily obtained either via sequential or one-pot mechanochemical methods. Computational modelling methods reveal that the HOCs are thermodynamically driven to form and that their mechanical properties strongly depend on the composition and intermolecular forces in the crystal, offering untapped potential for optimizing material properties.